Novel 1-(4-chlorophenyl)-3-(2-ethoxyphenyl)triazene ligand: Synthesis, X-ray crystallographic studies, spectroscopic characterization and DFT calculations - Fatemeh Valinia; Nasrin Shojaei; Parisa Ojaghloo (Chemical Review and Letters, 2019)
In the present work, a combined theoretical and experimental investigation on the properties of 1-(4-chlorophenyl)-3-(2-ethoxyphenyl)triazene is reported. The optimized geometry was calculated by B3LYP method using 6-311++G(2d,p) as a large basis set. The FT-IR spectrum was calculated at this level of theory, and was interpreted in terms of potential energy distribution (PED) analysis. The scaled theoretical frequencies were in line with the experimental ones. Furthermore, natural bond orbital (NBO) and atoms in molecules (AIM) theories were used to characterize intra-molecular hydrogen bond. The low value of charge transfer and the absence of bond critical point between O···HN show that there is not intra-molecular hydrogen bond.